Prevalence shoulder pain in eliteswimmers - Andreánský, M.; Líška, D.; Belicka, P. (Zdravotnícke listy, 2018)
In our work, we aimed observed the incidence of shoulder pain in swimmers. The aim of the work was to determine the prevalence of shoulder pain in swimmers and to specify the factors that could contribute to the development of this pain. An important role in the prevention or treatment of the shoulder injury plays the kinematics itself and the biomechanics of the shoulder knitting. The kinematics and biomechanics themselves require a swimmer in the correct technical design for sports performance. Breaking this technique may lead to higher prevalence and incidence of individual injuries. The method we used was a questionnaire. We have been able to find out more about the pain of shoulder plexus. The questions were focused on finding data on training benefits, regeneration, choosing a painkiller. As a complement to the questionnaire, we have chosen resistance tests for the rotator cuff. We processed the data in the form of graphs. Shoulder sting pain occurred in 19 swimmers, which is 60% of our sample. Resistance tests did not correlate with the incidence of pain reported in the questionnaire. The load and regeneration ratio has been found to be inadequate in swimmers because of their age and training. Based on our work, swimming clubs should focus in the future on the quality of training cycles, with the emphasis on working with professionals, already within the framework of prevention.